Workspace analysis of a multifingered metamorphic hand - Cui, Lei; Dai, J.; Wang, D. (IEEE Press, 2009)
This paper introduces a metamorphic palm from an artifact of origami folding and presents a novel robotic hand with the palm that makes the hand adaptable and reconfigurable leading to a new philosophy in design based on inspiration from art as artmimetics. The orientation of the new robotic hand is enhanced by the additional motion of the palm and the workspace of the robotic finger is enlarged by the palm workspace. To analyze this integrated workspace, this paper introduces finger-operation planes to relate the finger operation to the palm motion and its configuration. The normals of these operation planes are then used to construct a Gauss map. Adding an additional dimension, a four-dimensional ruled surface can be generated from this map to illustrate the orientation change. With the change of palm configurations an orientation manifold can be developed from the orientation ruled surfaces. The workspace analysis is further developed by introducing a triangular palm workspace. This workspace evolves into a helical surface and is further developed into a four-dimensional representation. Incorporated with three finger-workspaces, the workspace of the robotic hand is hence produced.